Television News, Political Choices and Voting Behaviours in Anand Nagar Slum Bhopal: An Ethnography Study (Indian Journal of Mass Communication and Journalism (IJMCJ), 2024)
This paper examines the diverse relationships of different publics within Anand Nagar slum with these news programs and political discourses, detailing how many men and women in the slum watched and engaged with what they see as political communication on television. Following the qualitative methodological approaches specifically ethnography conducted in slums of Bhopal, the paper detailed how youth watch television news for political information and does these watching has little correlation to their electoral choices and voting decisions in their everyday lives.